Hubungan antara Asertivitas dengan Kesejahteraan Psikologis pada Dewasa Awal Suku Jawa - Filia Dasiska Septi Arisandhi Tarigan; Maria Nugraheni Mardi Rahayu (Universitas Muhammadiyah Metro, 2026)
Javanese culture, which emphasizes social harmony and politeness, often makes it difficult for individuals to express their opinions, which can ultimately affect their psychological well-being. This study aims to determine the relationship between assertiveness and six dimensions of psychological well-being in early adult Javanese individuals. This study uses a quantitative method with a correlational design to examine the relationship between assertiveness and psychological well-being. There were 202 early adult Javanese individuals participating in this study, selected using incidental sampling technique. The measurement tools used were the Alberti and Emmons assertiveness scale (Î± = 0.812) and Ryff's Psychological Well-Being Scale (Î± = 0.786). The results showed a significant positive relationship between assertiveness and all dimensions of psychological well-being, including (r = 0.571; p < 0.05), environmental mastery (r = 0.634; p < 0.05), personal growth (r = 0.675; p < 0.05), positive relationships with others (r = 0.684; p < 0.05), life purpose (r = 0.647; p < 0.05), and self-acceptance (r = 0.722; p < 0.05). These findings indicate that the higher an individual's level of assertiveness, the higher their psychological well-being. The results of this study emphasize the importance of developing assertiveness as an effort to improve psychological well-being in the Javanese cultural contextÂ